Lope de Vega's Villancico in «El Amor enamorado»: Dramatic Functions and the Discovery of an Unpublished Manuscript (Castilla. Estudios de Literatura, 2021)
The little attention paid by copyists and printers to the musical stage directions of the Spanish Siglo de Oro theatre has made go unnoticed certain poetic-musical strategies that Lope de Vega used to generate complex meanings interrelated with the plot. This work analyzes the villancico “A la gala de Febo” from the play El Amor enamorado, traces sources and influences and fills critical gaps to such an extent that reports the discovery of an anonymous manuscript found in the Biblioteca de Catalunya with the music of Lope’s text, which until now was believed to be lost.
Keywords: El Amor enamorado; Lope de Vega; villancico; theatre; music